Mathematical modelling and transcriptional characterisation of intratumoral regulatory T cell sub-populations - Muzhingi, I (2023)
Regulatory T cells (Tregs) suppress harmful immune responses and help prevent autoimmune reactions. However, high densities of Tregs accumulate in solid tumours and contribute to the suppression of anti-tumor responses. The targeting of intratumoral Tregs via antibody-mediated blockade/depletion is a promising cancer treatment strategy but remains ineffective and induces adverse events. Some of these challenges can be addressed by conducting extensive transcriptional profiling of intratumoral Tregs and quantitatively assessing Treg migration dynamics to identify appropriate therapeutic targets and guide the development of safe and effective Treg-targeting therapeutics.